Implementasi Program Electronic Filing (E-Filing) Dalam Upaya Peningkatan Kepatuhan Wajib Pajak Orang Pribadi Kota Pontianak Kalimantan Barat Dengan Pemahaman Menuju Era Ekonomi Digital - Sri Haryaningsih; Juniwati Juniwati (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The use of digital technology (Electronic Digital Services) has created a new government bureaucratic mechanism, which is known as the Electronic Government (e-Government). There are so many policies that use an e-government system, one of which is the e-Filing program in the tax sector. E-Filing aims to provide convenience in submitting the Personal Taxpayer's Annual Income Tax Return. This study aims to determine how the implementation of the e-Filing program in the Effort of Increasing Individual Taxpayer Compliance in Pontianak City, West Kalimantan Province. The research method used is a descriptive research method with a qualitative approach. The data collection technique is carried out by interviewing, observation and recording documents related to the filing of the Annual Tax Return of Individual Taxpayers. The data obtained were then analyzed qualitatively by examining all the data that had been collected which was supported by the results of interviews with the theoretical approach to the model of policy implementation by Donald Van Meter and Carl Van Horn, who argued that the success of a policy was influenced by the size and policy objectives, resources, communication between variables. the executing agency, the characteristics of the executing agency, the social, the economic and political environment, and the attitudes of the executors / dispositions. From the research results, it had been seen that the implementation of the e-Filing program in the Effort to Improve Individual Taxpayer Compliance in Pontianak City, West Kalimantan Province, basically has not run optimally. This is because the provision of resources is still not optimal and the social, the economic and political conditions are less supported